Subcritical propagation of fatigue assisted cracks in structural steel ASTM A36 (SCIÉNDO INGENIUM, 2023)
In this work, the subcritical propagation of fatigue-induced cracks in ASTM A36 steel was investigated using the Paris law (dA/dN) = C(ΔK)m, which relates the speed of crack propagation and the stress intensity factor. KIC. This model can be used to predict the useful life of components or structures that are subjected to fatigue. Three specimens were tested in a three-point bending fatigue machine, the machine is equipped with a computer data acquisition system. To monitor the propagation of the crack, the Playa mark technique was used. With the data obtained, the curve a vs N (crack depth vs number of cycles) was plotted, and from this curve the dA/ curve was obtained. dN vs a (crack advancement speed vs crack depth), and the graph dA/dN vs ΔK, to determine the KIC stress intensity factor, the Newman-Raju equation was used. This analysis resulted in the Paris equation constants: C = 4.0 x 10 -6 m/cycle and m = 0.7, which are within the published range. The hardness of the material was also measured.
Keywords: stress intensity factor; fatigue; subcritical crack propagation